The U.S. Structural Transformation and Regional Convergence: A Reinterpretation - Caselli, Francesco; Coleman II, Wilbur John (Journal of Political Economy, 2001)
We present a joint study of the U.S. structural transformation (the decline of agriculture as the dominating sector) and regional convergence (of southern to northern average wages). We find empirically that most of the regional convergence is attributable to the structural transformation: the nationwide convergence of agricultural wages to nonagricultural wages and the faster rate of transition of the southern labor force from agricultural to nonagricultural jobs. Similar results describe the Midwest's catch-up to the Northeast (but not the relative experience of the West). To explain these observations, we construct a model in which the South (Midwest) has a comparative advantage in producing unskilled laborintensive agricultural goods. Thus it starts with a disproportionate share of the unskilled labor force and lower per capita incomes. Over time, declining education/training costs induce an increasing proportion of the labor force to move out of the (unskilled) agricultural sector and into the (skilled) nonagricultural sector. The decline in the agricultural labor force leads to an increase in relative agricultural wages. Both effects benefit the South (Midwest) disproportionately since it has more agricultural workers. With the addition of a less than unit income elasticity of demand for farm goods and faster technological progress in farming than outside of farming, this model successfully matches the quantitative features of the U.S. structural transformation and regional convergence, as well as several other stylized facts on U.S. economic growth in the last century. The model does not rely on frictions on interregional labor and capital mobility, since in our empirical work we find this channel to be less important than the compositional effects the model emphasizes.